PEMANFAATAN SISTEM INFORMASI BAGI PERANCANG PERATURAN PERUNDANG-UNDANGAN - ., M. Aliamsyah (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
Information system can make someone easier in carrying out or completingthe tasks. Information system develops in line with human civilization, usingany available facilities at that time, with the use of stone and walls ofcaves in ancient times up to the usage of information technology today.A legislation information system is a system created as a tool or a source ofinformation of legislation that will benefit the legal drafter in the preparationof legislation and for people who want to find legal information andlegislation. In fact, the legal drafter in supporting their work has notoptimally utilized the information system of legislation that exists today.That situation caused by other factors such as the level of ability andwillingness of the utilization of information system of legislation that isstill lack and the absence of regulatory information system legislation thatcreated by adapting a standard of accuracy and validity of the data.